Design and analysis of multi-angle diffraction efficiency distribution for all-dielectric transmissive grating - Zhu, Jiaze; Jia, Mian; Feng, Huizhen; Gu, Manna; Huang, Wenkang; Tian, Ying; Xu, Jianfeng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
This paper presents the design of a C-shaped all-dielectric metasurface. The C-shaped dielectric structure and its substrate materials are Si and SiO2, respectively. This unit structure enables independent control of the amplitude and phase of cross-polarized transmitted terahertz electromagnetic waves. By using parameter scanning method, four different unit structures were optimized at 0.1 and 1 THz, achieving unit phase distributions with a 45° interval within the range of 0° to 180°. Additionally, a 180° phase jump occurs when the unit structure rotates by 90°, achieving full phase control over the 360° range. By adjusting the orientation of the unit structure, arbitrary amplitude control can also be achieved. The highest transmission coefficients for the unit structures at 0.1 and 1 THz are 0.62 and 0.56, respectively. To verify the control capability of the designed unit structure on transmitted electromagnetic waves, metasurface gratings were designed based on these unit structures, enabling arbitrary control of diffraction angles and orders. At both frequencies, two different metasurface gratings were designed with diffraction orders of (m = +1) and (m = +1, +3). Near-field and far-field simulations of the super-grating structures were conducted using the finite integral method. The designed metasurface grating demonstrates effective control of cross-polarized transmitted waves, and its deflection angles conform to diffraction laws.
Optica Applicata, Vol. 55, 2025, nr 2, s. 225-239
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; grating; metasurface; optics